STUDY PROGRAM OF FISHERMEN’S WIFE ON THE BUSINESS PROCESSING OF FISH CHIP CRACKER CORNER VILLAGE HILL REGENCY OF BENGKALIS REGENCY RIAU PROVINCE - Arifin, Husni; Hamid, Hamdi; Arief, Hazmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study attempts to evaluate the objectives of the fishermen wife empowerment program and household income of fish chip crackers in Bukit Batu Village, Bengkalis Regency, Riau Province. The result of the research shows that the implementation of fishermen wife empowerment program is good, it can be seen from the condition of fish cracker processing business which has changed after the establishment of program by Marine Fisheries Department, among others: 1) the existence of business capacity improvement, 2) the improvement of business quality, 3) and the institutional strengthening that occurs in fish cracker processing business.In addition, the fishermen fishermen empowerment program also affects the income of fishermen households who participate in the empowerment of fishermen fish cracker empowerment program, on household income shown in 2017 household income outside fishing fish cracker business processing amounting to IDR. 135.600.000. and fish cracker business income revenues increased revenue amounted to IDR.59.510.400. resulting in the addition of household income of fishermen amounting to IDR.195.110.400. in 2017.And the contribution of fishermen's wife's income was 44% of the income received by fishermen's households processing fish crackers in Bukit Batu Village, Bengkalis Regency in 2017 Keyword: empowerment, fishermen’s wife, processing, income